Mathematical Proving Ability of Pre-service Teachers in Online and Blended Learning - Siska Pramasdyahsari, Agnita; Buchori, Achmad; Rasiman, R (KnE Social Sciences, 2022)
Mathematical proving is an important ability to learn. However, mathematics pre-service teachers often find this skill difficult. This research aimed to describe the mathematical proving ability of mathematics pre-service teachers in an online classroom and in the blended classroom. A descriptive mixed methods approach was used. A mathematical proving test was used to collect the data. The results showed that the average score of mathematical proving ability from the blended classroom was 82.6 (categorized as high). Meanwhile, the average score of mathematics pre-service teachers in the online classroom was 65.4 (categorized as intermediate). Given these findings, there is a significant need to improve the mathematical proving ability of the mathematical preservice teachers in the online classroom by enhancing the conceptual understanding of group properties and ensuring the teachers are accustomed to practicing proving tasks. Keywords: mathematical proving, online learning, blended learning, mathematics pre-service teachers, group theory